Grafting onto an Appropriate Rootstock Reduces the Impact on Yield and Quality of Controlled Deficit Irrigated Pepper Crops - Ramón Gisbert-Mullor; Nuria Pascual-Seva; María Amparo Martínez-Gimeno; Lidia López-Serrano; Eduardo Badal Marín; Juan Gabriel Pérez-Pérez; Luis Bonet; Yaiza Gara Padilla; Ángeles Calatayud; Bernardo Pascual; Salvador López-Galarza (Agronomy, 2020)
In this study, hybrid pepper rootstock NIBER® is tested for its ability to overcome water stress situations under soil conditions. The impact of deficit irrigation (DI) on yield and fruit quality, irrigation water use efficiency is evaluated, and consequently, the agronomic impact of employing water-stress tolerant rootstock is compared to ungrafted pepper plants. For this purpose, plants of the California-type sweet pepper ‘Maestral F1’ grafted onto NIBER® underwent a sustained DI regime during seasons 2018 and 2019 and were compared to their respective controls. Plants were drip-fertirrigated, and volumetric soil water content was continuously monitored by capacitance sensors. Gas exchange and leaf water potential measurements were taken early in the morning and midday 58, 79, and 114 days after transplanting. Plant and fruit dry biomass, marketable quality, blossom-end rot incidence and harvest index were also determined. For consecutive years, our results confirmed that grafting a pepper cultivar onto an appropriate rootstock (NIBER® in this case) as part of a DI strategy can overcome the negative effects of sustained water stress conditions. The plant biomass production and fruit yields of grafted plants were less affected by DI due to less sensitivity to water stress. This can be attributed to a less marked reduction in shoot dry weight in the grafted plants, which allowed greater whole photosynthesis by maintaining sink activity compared to ungrafted plants.